Widowhood in modern India - Nayar,P.K.B; Nayar, P. K. B., 1929-; Centre for Gerontological Studies (Trivandrum, India) (Delhi : Women Press, 2006)
On widows in India presented at the first national seminar of Centre for Gerontological Studies, Trivandrum.
Includes bibliographical references.
Keywords: Widows -- India -- Congresses